PREVALENSI KARAKTERISTIK PASIEN ASMA DI POLI PARU RSU. MADANI MEDAN: PREVALENCE OF CHARACTERISTICS OF ASTHMA PATIENTS AT THE PULMONOLOGY CLINIC OF MADANI GENERAL HOSPITAL MEDAN - Refi Sulistiasari (Fakultas Kedokteran Universitas Islam Sumatera Utara, 2026)
Asthma prevalence currently tends to increase in urban areas due to environmental pollution and lifestyle changes, contributing to 30% of deaths from chronic respiratory diseases based on the 2023 Medan City Health Profile. However, the variability of patient characteristics at the Pulmonology Clinic of Madani General Hospital due to pollution and sociodemographics has not been reported for the most recent period. This study aims to obtain prevalence data on the characteristics and sociodemographics of asthma outpatients at the Pulmonology Clinic of Madani General Hospital Medan. The study utilizes a descriptive research design with a cross-sectional approach among asthma outpatients at the Pulmonology Clinic of Madani General Hospital Medan. Univariate data analysis was performed on the characteristics of 50 asthma patients. The gender was dominated by males (58%), the predominant age group was 46–55 years old (34%), and the majority held employed status (70%). Genetic factors contributed strongly, with a family history of asthma at 60%, while the history of allergies was low (24%), indicating a non-atopic phenotype. Furthermore, the level of asthma control was categorized with uncontrolled status reaching 46% and partially controlled at 36%. Conclusion of this study are the dominant demographic consists of productive-aged males with a tendency toward a non-allergenic asthma phenotype influenced by genetic factors. The poor level of asthma control, affecting nearly half of the population, highlights the urgent need for treatment adherence evaluation and more intensive clinical education AbstrakAsma saat ini cenderung meningkat di perkotaan akibat polusi lingkungan dan perubahan gaya hidup, berkontribusi pada 30% kematian akibat penyakit pernapasan kronis berdasarkan Profil Kesehatan Kota Medan 2023. Namun, variabilitas karakteristik pasien di Poli Paru RSU Madani akibat polusi dan sosiodemografi belum ada dilaporkan untuk periode terbaru. Penelitian ini bertujuan mendapatkan data prevalensi karakteristik , sosiodemografi pasien asma rawat jalan di Poli Paru RSU. Madani Medan. Desain penelitian deskriptif dengan pendekatan Cross-sectional pada pasien asma rawat jalan di poli Paru di RSU Madani Medan. Analisa data univariat terhadap karakteristik terhadap 50 pasien asma. Jenis kelamin didominasi laki-laki (58%), kelompok usia 46–55 tahun (34%), dan berstatus bekerja (70%). Faktor genetik berkontribusi kuat dengan riwayat keluarga sebesar 60%, sedangkan riwayat alergi rendah (24%) yang mengindikasikan fenotipe non-atopi. Selain itu, tingkat kontrol asma tergolong status tidak terkontrol mencapai 46% dan terkontrol sebagian sebesar 36%. Kesimpulan peneiltian ini adalah bahwa jenis kelamin yang mendoninasi laki-laki usia produktif dengan kecendungan fenotif asma non- alergenik yang dipengaruhi faktor genetik. Tingkat kontrol asma yang tidak terkontrol/terkontrol sebagian mencapai hampir separuh populasi menegaskan perlunya dilakukannya evaluasi kepatuhan terapi dan edukasi klinis yang lebih intensif.